Measuring Cognitive Load in Blended Laboratory Setting: Toward Enhanced Learning in Chemistry - D. Urbano, Roselle; G. Caballes, Dennis (International Journal of English Literature and Social Sciences (IJELS), 2020)
The present study explored on the effectiveness of blended laboratory environment in performing activities and it determined whether a significant relationship exists between the cognitive load levels and the enhanced learning of freshman students in Inorganic Chemistry via blended laboratory setting. Freshman students enrolled in Bachelor of Secondary Education(n=77) were the respondents of the study. Seven blended laboratory activities were performed. Pretest and posttest were administered and evaluated and their cognitive loads. The findings showed a significant difference between the pretest and posttest means results of the respondents and these results imply that the students learned conceptually by performing activities using blended laboratory. Among the seven activities performed, only one activity focusing on atomic models has a significant relationship to the performance in Chemistry (r = 0.235). This seems to suggest that the more the students were challenged with the situation the better they were able to understand the concept and were able to employ more attention. The results implied that blended laboratory setting can be used as a method in teaching concepts in Inorganic Chemistry to fully optimize more the potential of education technology.